Synchronous bilateral breast carcinomas with divergent radiographic presentations: Radiologic-pathologic correlation of invasive mucinous and ductal carcinomas - Lena Caron; Evelyn May; Ashley Cimino-Mathews (Elsevier, 2015)
The differential diagnosis of well-circumscribed breast masses on imaging includes mostly benign tumors. A potential pitfall in diagnostic breast imaging is that 10-20% of malignancies appear as lesions with benign imaging characteristics. This report presents a case of synchronous bilateral breast masses, one of which demonstrated benign imaging characteristics (well circumscribed) and the second of which demonstrated suspicious imaging characteristics (spiculated and indistinct). After radiologic-pathologic correlation, it was found that the well-circumscribed mass of the right breast was an invasive mucinous carcinoma, and the spiculated indistinct mass of the left breast was an invasive ductal carcinoma. This highlights a possible hazard of diagnostic imaging in the setting of benign-appearing lesions, and underscores the importance of radiographic-pathologic correlation in the evaluation of breast masses.